'An Awkward Engine': Captain Philip Broke's troublesome relationship with the carronade. Issue 3 (2nd July 2016) - Bibbings, Martin
Abstract : From its first introduction in the late 1770s during the American Revolutionary War the carronade was enthusiastically embraced by the Admiralty for use in its warships, dramatically increasing the firepower and effectiveness of even the smallest vessels. Diminutive in size and weight compared to conventional long guns it was capable of firing heavy-calibre shot, and required only a small crew to operate. Philip Broke, Captain of the 38-gun frigate HMS Shannon valued the carronade highly and replaced much of his ship's original upper deck armament with these weapons. However, its advantages of size and weight relative to calibre were also the cause of its biggest problems. Broke discusses many of these issues in his correspondence at the Suffolk Record Office including his review of Sir Howard Douglas's manuscript for his Treatise on Naval Gunnery and in his dealings with the Board of Ordnance. This article re-evaluates the use and effectiveness of the carronade in light of Broke's comments.